2015
DOI: 10.1523/jneurosci.2620-14.2015
|View full text |Cite
|
Sign up to set email alerts
|

Triggering Receptor Expressed on Myeloid Cells 2 (TREM2) Deficiency Attenuates Phagocytic Activities of Microglia and Exacerbates Ischemic Damage in Experimental Stroke

Abstract: Clearing cellular debris after brain injury represents an important mechanism in regaining tissue homeostasis and promoting functional recovery. Triggering receptor expressed on myeloid cells-2 (TREM2) is a newly identified receptor expressed on microglia and is thought to phagocytose damaged brain cells. The precise role of TREM2 during ischemic stroke has not been fully understood. We explore TREM2 in both in vitro and in vivo stroke models and identify a potential endogenous TREM2 ligand. TREM2 knockdown in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
279
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 303 publications
(290 citation statements)
references
References 46 publications
11
279
0
Order By: Relevance
“…6). In keeping with our macroscopic observation that infarct areas in PAP‐1‐treated mice are shrunken on day‐8 after reperfusion MCAO and not swollen like in mice where phagocytosis is impaired (e.g., TREM2 −/− mice29), PAP‐1 treatment at both the low and the high dose did not reduce the percentage of CD68 + phagocytes closely contacting TUNEL + cells or containing TUNEL + material on day‐8. However, in animals treated with the higher dose of PAP‐1, overall fewer CD68 + phagocytes and less TUNEL + staining was observed (not shown), but the percentage of association/internalization was not significantly changed (Fig.…”
Section: Resultssupporting
confidence: 87%
“…6). In keeping with our macroscopic observation that infarct areas in PAP‐1‐treated mice are shrunken on day‐8 after reperfusion MCAO and not swollen like in mice where phagocytosis is impaired (e.g., TREM2 −/− mice29), PAP‐1 treatment at both the low and the high dose did not reduce the percentage of CD68 + phagocytes closely contacting TUNEL + cells or containing TUNEL + material on day‐8. However, in animals treated with the higher dose of PAP‐1, overall fewer CD68 + phagocytes and less TUNEL + staining was observed (not shown), but the percentage of association/internalization was not significantly changed (Fig.…”
Section: Resultssupporting
confidence: 87%
“…It has previously been reported that TREM2 is capable of binding microbial and damage-associated molecular signatures found on bacteria (41,42), lipids exposed during axonal injury (23,43), and nucleic acid released from dying cells (29). Here, we report apoE as a novel TREM2 ligand.…”
Section: Alzheimer Disease (Ad)mentioning
confidence: 67%
“…Overexpression of microglial TREM2, however, suppressed this excessive cytokine production under the same stimulatory conditions (27). Furthermore, TREM2 deficiency has been shown to result in reduced phagocytic activity of apoptotic neurons (24,28,29), A␤ (50,51), and E. coli (51) by microglia. A recent report elegantly demonstrated a direct role for TREM2 in facilitating phagocytosis both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yenari et al found decreased phagocytosis and infarcted brain tissue resorption in triggering receptor expressed by myeloid cells 2-deficient mice compared with wild-type mice subjected to experimental stroke. 9 Triggering receptor expressed by myeloid cells 2 further seems to be essential for neurological recovery in a stroke model.…”
Section: Midori Yenari United States Addressed the Role Of Triggerimentioning
confidence: 99%